Is Concentrated Urine PCR Test Valuable to Detect Genital HPV Infection - Aksakal, Boran; Acar, Osman; Nadirova, Narmin; Apa, Alara; Ozturk, Harika Bodur (LIPPINCOTT WILLIAMS \& WILKINS, 2024)
72nd Annual Clinical and Scientific Meeting of the American-College-of-Obstetricians-and-Gynecologists, San Francisco, CA, MAY 17-19, 2024